Norman Mailer - the most influental critic of contemporary reality in the second half of the twentieth century - Potočnik, Jasna (Acta neophilologica, 2013)
Norman Mailer, one of the most influential authors of the second half of the twentieth century, faithfully followed his principle that a writer should alsobe a critic of contemporary reality. Therefore, most of his works portray the reality of the United States of America and the complexities of the contemporary American scene. Mailer described the spirit of his time - from the terror of war and numerous dynamic social and political processes to the 1969 moon landing. Conflicts were often in the centre of his writing, as was the relationship between an individual and the society; he speaks of political power and the dangerous power of capital, while pointing to the threat of totalitarianism in America. Mailer spent his entire career writing about violence, power, perverted sexuality, the phenomenon of Hitler, terrorism, religion and corruption. He continually pointed out that individuals were in constant danger of losing freedom and dignity.
Keywords: American literature; ameriška književnost; literarni žurnalizem; literary journalism; Mailer, Norman, 1923-2007; political power; politics; politika